Repositioning Asia from bubble to sustainable economy - Kotler, Philip; Kartajaya, Hermawan (Singapore ; New York : John Wiley and Sons (Asia), 2000)
This book is divided into three parts: Background; Transforming the Nations; and Revitalizing the companies.
Keywords: Economics; Asia; Industrial management; Industrial management -- Asia; Asia -- Economic conditions -- 1945-; Asia -- Economic policy -- Decision making